THE LONG PERIOD EFFECT OF TWILIGHT ON THE ABILITY OFSEEING CRESCENT - BANDAR, BATOOL (Iraqi Journal of Science, 2024)
Twilight is a light which appears in the horizon before the sunrise and after thesunset .This research is about the count of long period of twilight after the sunset fora day born of crescent in Iraq for the city of Baghdad , Mousl , Basrah for manyyears and for months of blessed Ramadan and Shawal . Studying the changes periodof astronomic twilight on the long of months of year for three cities . It is found thatthe different between the bigger and smaller period for twilight on the long ofmonths of year arrives to (22 ) minute in Baghdad and in Mousl (25 ) minute , inBasrah (19 ) minute . As well studying elements seeing crescent for this month .It isfound that there is a reflected relation between the long period of twilight and theprobability seeing crescent. When we take period of twilight (79 )minute , theprobability is (39.43% ) and it is less than the value of probability to see . There is areflected relation between the long period twilight and period of stay crescent. Whenwe take period twilight (79 ) minute , period stay crescent is (18.52 ) minute . It isless than the value desired stay for seeing crescent as it showed the long periodtwilight is certainly firm on the round seasons of year with a simple different . It hasnot a huge effect on the probability of seeing crescent